Engaging Graduate Students in the Online Learning Environment: A Universal Design for Learning (UDL) Approach to Teacher Preparation - Marla J Lohmann; Kathleen A Boothe; Andrea R Hathcote; Amy Turpin (Networks: An Online Journal for Teacher Research, 2018)
Today’s classroom is more diverse than ever; it is imperative that universities find solutions for meeting these diverse learning needs. One potential solution is Universal Design for Learning (UDL), which is a promising practice in the K-12 classroom. UDL is based on the idea that diversity among students is predictable and systematic adjustments to the curriculum should be made based on that predictability. While there is strong research supporting the use of UDL for traditional K-12 classrooms, there is little research regarding its implementation in the online university teacher preparation classroom. This study explores the use of UDL for increasing student engagement in online Special Education teacher preparation courses. The authors seek to expand on the literature regarding the use of UDL in the university setting by examining the impact of engagement strategies in online Special Education teacher preparation courses. Results of a case study utilizing a qualitative survey of online teacher preparation candidates are examined.
Keywords: Universal Design for Learning; Online Learning; Student Engagement; Teacher Preparation; College Teaching